2014
DOI: 10.1097/mpa.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Does a Family History of Pancreatic Ductal Adenocarcinoma and Cyst Size Influence the Follow-up Strategy for Intraductal Papillary Mucinous Neoplasms of the Pancreas?

Abstract: Patients with 1 first-degree relative with PDAC can be followed up using the same criteria for patients without a family history. Special attention should be paid to IPMN progression and malignant transformation in patients with IPMNs of greater than or equal to 30 mm, but cyst size need not be considered when determining follow-up strategies for patients with IPMNs of less than 30 mm without mural nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The 15 studies included in the qualitative analysis are listed in Table . All but one of these studies were retrospective; six analysed Western populations (Europe and USA), whereas nine were conducted in Asia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 15 studies included in the qualitative analysis are listed in Table . All but one of these studies were retrospective; six analysed Western populations (Europe and USA), whereas nine were conducted in Asia.…”
Section: Resultsmentioning
confidence: 99%
“…Data on disease progression were reported in only nine of 15 studies, with heterogeneous definitions, and disease progression was observed in 257 of 580 patients (44·3 (range 30–52) per cent).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 It is unknown whether for example in the case of BD-IPMNs the same criteria for resection apply in HRIs compared to sporadic cases. 28 A recent study showed that cystic lesions diagnosed in HRIs with a known mutation are more prone to progress compared to those discovered in FPC individuals, although this latter group had a significantly higher prevalence of cystic lesions. 29 There is also evidence of a high rate of lymph node involvement and poor prognosis in HRIs with PDAC even with very small lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Nehra et al58 showed that concurrent PDAC in patients who underwent resection of IPMN were more commonly observed in those with than in those without a family history of PDAC (11.1% vs 2.9%, respectively; P =.02). Meanwhile, Mandai et al59 showed that the frequency of concomitant PDAC in patients with BD‐IPMN or mixed IPMN was significantly higher in patients with than in those without a family history; however, median age of the patients with a family history was significantly higher than in those without a family history. To exclude the influence of age, Mandai et al carried out another comparison in which they limited the age of patients to ≥70 years and, as a result, the frequency of concomitant PDAC was not significantly different between these two groups.…”
Section: Surveillance For Ipmn Without Pancreatectomymentioning
confidence: 99%